An integrated knowledge translation project to develop, implement, and evaluate a train-the-trainer program at a community rehabilitation program in Tamil Nadu, India. Issue 26 (18th December 2021) - Hunt, Matthew; Ponnusamy, Ramasubramanian; Goulet, Anik; Anthonypillai, Chamila; Muthukaruppan, Sankar Sahayaraj; Bharathwaj, Aravind; Thomas, Aliki; Archambault, Philippe S.; Garnett, Crystal; Storr, Caroline; Krishna, Dinesh
Abstract: Purpose: This project aimed to develop, implement and evaluate a train-the-trainer initiative for community rehabilitation workers (CRWs) and rehabilitation specialists within a community rehabilitation program for children with delayed development in Tamil Nadu, India. Methods: Guided by the Knowledge to Action framework, non-governmental and academic partners collaboratively developed two 2-day workshops for (1) rehabilitation specialists and (2) CRWs. Outcomes were evaluated using mixed methods, with pre and 2.5-months post surveys (59 participants) and three focus groups (17 participants) involving trainers and trainees (including rehabilitation specialists and CRWs). Results: There were significant increases in the CRWs' self-perception of their capacity to assess comprehension, provide explanations, respond to questions, adjust teaching, motivate learners, communicate effectively, and provide feedback. Significant changes were noted for rehabilitation specialists in five of seven domains, and for rehabilitation specialist leads in six of seven domains. Participants appreciated the interactive training style, and the use of immersive methods such as role play, though noted challenges when instructions were unclear or when they felt that material was more theoretical. Conclusions: This collaboratively developed train-the-trainer project demonstrates the value of such an intervention, provides an example of how a tailored program can be developed, and suggests the importance of stakeholder-driven design processes. Implications for Rehabilitation: The ability to provide effective training is a core skill set for people engaged in community-based rehabilitation (CBR) programs, yet examples of initiatives to train trainers are lacking, as is their evaluation. This project demonstrates the value of a collaborative and tailored train-the-trainer program to support community rehabilitation workers and rehabilitation specialists in their training roles within a CBR program in India. A stakeholder-driven design process supported by a collaboration between non-governmental organization and academic partners enhanced the capacity to develop, implement and evaluate the train-the-trainer program.